2012
DOI: 10.1371/journal.pone.0032695
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Weaknesses of Immunotherapy for Advanced Non-Small-Cell Lung Cancer: A Meta-Analysis of 12 Randomized Controlled Trials

Abstract: BackgroundLung cancer is one of the leading causes of cancer death worldwide. Non-small-cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancers. Immunotherapy has yielded no consistent benefit to date for those patients. Assessing the objective efficacy and safety of immunotherapy for advanced NSCLC patients will help to instruct the future development of immunotherapeutic drugs.Methodology and Principal FindingsWe performed a meta-analysis of 12 randomized controlled trials including 3134 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
(79 reference statements)
0
22
0
2
Order By: Relevance
“…In addition, pathologic studies have found that patients with intense lymphocytic infiltration of their solid tumors have longer survivals rates than those who do not (36). These and other related observations led to extensive efforts to develop vaccines and other immunologic approaches in an attempt to enhance the immune system’s effect against invasive cancers (79). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, pathologic studies have found that patients with intense lymphocytic infiltration of their solid tumors have longer survivals rates than those who do not (36). These and other related observations led to extensive efforts to develop vaccines and other immunologic approaches in an attempt to enhance the immune system’s effect against invasive cancers (79). …”
Section: Introductionmentioning
confidence: 99%
“…The aim of immunotherapy is to eliminate cancer cells through the activation of host immunity by using biological response modifying polysaccharides, monoclonal antibody and cytokines. (Wang et al, 2012). Interleukin-12 is aheterodimeric cytokine composed of two subunits (p35 and p40) both of which are required for the secretion of the active form of IL-12p70, primarily produced by APCs and exert pleiotropic effects on immune effector cells (Tamandani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy provides a new clinic strategy to enhance the immune function of tumor immunity. After activation by stimulated DCs, auxiliary T lymphocytes and CTLs are capable of killing tumors, which is the theoretical basis of tumor vaccines (Wang et al, 2012). DCs based anti tumor immunotherapy have strong ability to stimulate naïve T lymphocytes and induce effective anti-tumor responses (Guermonprez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The stereochemistry of such carbohydrate ligands is diffi cult to control, and the products are diffi cult to purify. A frequently used alternative for carbohydrate ligands are antibodies raised against DC receptors (i.e., integrin CD11c/CD18 [ 55 ], Fc receptors [ 67 ], DEC-205 [ 7 ], DC-SIGN [ 68 ] and MR [ 69 ]), but these, even when humanized, may still elicit adverse immune responses that decrease the effi ciency of treatment and induce auto-immune side-effects [ 70 ].…”
Section: Poly(ethylenimine)mentioning
confidence: 99%